A Stochastic analytic hierarchy process - based methodology for supplier selection problem in group context - Cruz, Mar Buted (College of Engineering, University of the Philippines Diliman, 2015)
The supplier selection problem (SSP) is a complex decision making process due to the different parameters and various aspects needed to be considered before decisions are made. Hence, a group approach approach to SSP is encouraged especially that stakeholder approach, and inter-firm trusts and cultural considerations in supplier selection are increasingly becoming important. a group approach in decision making normally produces better or more desirable results. This is possibly because groups have collective knowledge than individuals. However, a group approach in SSP is bounded by the issues of uncertainties/ impreciseness, inconsistencies, disagreements/non-consensus, incomplete preference information and preference maximization which are important to consider. Recognizing the importance of proper supplier selection, there is a need to develop group decision making methodology for supplier selection that maximizes consistency, consensus and preferences of supplier evaluators, and recognizes the degree of impreciseness and incompleteness of the supplier evaluators' preference information. The study proposed a stochastic Analytic Hierarchy Process-based methodology that provides linear programming model that does not only maximize consistency and consensus but also the preference of the supplier evaluators, and provides a reward-penalty system for preciseness/impreciseness and completeness/incompleteness of supplier evaluators' preference information. The proposed methodology was applied to actual business setting and then tested with secondary data. Results of the comparison experiments conducted favor the proposed methodology.